Benson's relaxation on anxiety and blood pressure in pregnant women with hypertension in pregnancy - Iffah, Uliy; Yulizawati, Yulizawati; Lisa, Ulfa Farrah; Insani, Aldina Ayunda; Fitria, Henni; Taufia, Dina (International Journal Labs, 2023)
Pregnant women with hypertension in pregnancy will experience physical and psychological discomfort, so complementary therapy is needed through self-suggestion techniques and spiritual therapy. This study aimed to determine the effect of Benson relaxation on anxiety and blood pressure of pregnant women with hypertension in pregnancy. This study used a Quasi-Experimental study with a randomized pretest-posttest control group design. The research sample was 46 respondents divided into two groups: the treatment and control groups. The study was conducted in 2 weeks. The results showed that there were 13 respondents whose anxiety scores were better. Statistical test results showed differences in the pre-test and post-test values with the Wilcoxon P-test value 0.002. The Mann-Whitney test showed a p-value of 0.046. Chi-square test results showed a p-value 0.011. Variable blood pressure: the average systolic pressure before being given the intervention was 141.39 mmHg to 133.65 mmHg after the intervention was given. Diastolic blood pressure from 91.30 mmHg to 86.70 mmHg. Statistics test results with paired t-tests showed a p-value 0.000, meaning that there were differences before and after the intervention. Benson relaxation influenced the decrease in anxiety, and declined blood pressure of pregnant women.